Exploring The Influence Of Islamic Learning And Parental Support On Students' Religious Morals: Does The Mediation Of Emotional Intelligence Matter? - khoiriyah, Ni'amatul; Mizani, Zeni Murtafiati; Daryono, Rihab Wit (Directorate of Research and Community Service, Universitas Negeri Yogyakarta, 2025)
This study aims to analyze Islamic Learning and Parental Support for Students' Religious Morals in MAN 1 Ngawi. The quantitative approach uses survey methods, which are conducted retrospectively to test the construction of Student Religious Morals variables. This study involved 278 MAN 1 Ngawi students, selected using probability sampling techniques. Data were collected through questionnaires with four variables: Islamic Learning, Parental Support, Emotional Intelligence as a mediator, and Students' Religious Morals. Data collection is done through Google Forms. Data analysis using Partial Least Squares Structural Equation Modeling PLS-SEM. The results showed that all indicators met the requirements of validity and reliability. The results showed that Islamic Learning and Parental Support had a significant impact on Students' Religious Morals. Emotional intelligence mediates the relationship between Islamic Learning and Students' Religious Morals. Implications in the context of religious education and the formation of children's moral character. Suggestions and recommendations include contextual studies that influence the development of students' emotional intelligence in Islamic Learning Parental Support supports the formation of students' religious morals.